Essays on Crime, Education, and Employment - Mancino, Maria Antonella (2018)
My thesis consists of three chapters that are motivated by policy-relevance and contribute to the study of crime choices among young individuals. Chapter 2 studies the determinants of youth crime using a dynamic discrete choice model of crime and education. We allow past education and criminal activities to affect current crime and educational decisions. We take advantage of a rich panel dataset on serious juvenile offenders, the Pathways to Desistance. Using a series of psychometric tests, we estimate a model of cognitive and social/emotional skills which feed into the crime and education model. This allows us to separately identify the roles of state dependence, returns to experience, and heterogeneity in driving crime and enrollment decisions among youth. We find small effects of experience and stronger evidence of state dependence and heterogeneity for crime and schooling. We provide evidence that, as a consequence, policies that affect individual heterogeneity (e.g., social/emotional skills), and those that temporarily keep youth away from crime, can have important and lasting effects even if criminal experience has already accumulated. Chapter 3 documents empirical facts about the criminal and legal labour sector for disadvantaged young individuals, and investigates the factors driving the transitions between sectors. I focus on the role of heterogeneity, earnings, human capital, and criminal capital in determining transitions across the criminal and legal labour sectors. The data I employ comes from the Pathways to Desistance Study. I find that disadvantaged young individuals face two low-quality employment alternatives. On the one hand, jobs in the legal labour sector are characterized by short average duration and low wages. Consistent with their low quality, these jobs present small returns to legal experience. Activity in the criminal sector presents similar features as legal jobs and it offers an earnings premium relative to the legal labour sector, which partially compensates for the inherent risk of the activity. I provide evidence that earnings in the criminal and legal labour sectors play a significant role on the transitions across sectors. This implies that choices in the criminal and legal labour sectors are strongly related and, as a result, they should not be studied in isolation of each other. Motivated by the findings in Chapter 3, Chapter 4 analyzes the legal employment and crime choices for disadvantaged youth. The labour market for this population group is usually studied ignoring the presence of the criminal sector, and yet a large share of them participate in crime. To study these outcomes jointly and explore how they relate, I build and estimate a two-sector search model allowing for a rich set of interactions between the two sectors. I estimate the model using monthly data from the Pathways to Desistance. Search frictions in the legal labour sector are found to be significant, with these individuals being offered low-quality legal jobs that are characterized by low earnings and large destruction rates. The criminal sector provides an attractive alternative to the legal labour sector, offering an earnings premium. Nevertheless, crime brings a higher probability of incarceration and fewer opportunities in the legal labour sector. I find that there are sizable interactions across sectors, and that policies in one sector can have important effects on the other sector. I provide evidence that policies targeting the legal labour sector (e.g., wage subsidy) can reduce crime and boost legal employment among disadvantaged youth. Furthermore, a policy that reduces the arrival rate of crime opportunities (e.g., via increasing the number of police), compared to extending the average sentence length, has the advantage of reducing crime without generating large increases in the incarcerated population